Focal Points of Architecture in Four Architectural Histories - Omid Shams (صفه, 2021)
The differences between various architectural histories partly have their roots in the historian’s ‘viewpoint’. The architectural historian’s view does not develop in a vacuum, and there is always a certain perspective involved. The historian’s viewpoint does influence his or her questions, testimonies, and interpretations, but more crucially it highlights or conceals certain layers of architectural knowledge.  The present paper studies some distinct viewpoints through which an architectural history views architecture. To do so, four distinct Western examples are chosen. Following a brief introduction of each example and its viewpoint through a descriptive and interpretive method, the historian’s point of view is discussed in each. The focus here is on the Gothic cathedral and one of its significant examples, Chartres Cathedral. The books and the focus of each one’s viewpoint are as follows: 1. History of Architecture on the Comparative Method (1905), views architecture as the artistic solving of building problems, and thereby Gothic cathedral as the outcome of the evolution of construction solutions; 2. The Story of Western Architecture (1979), adopts a Marxist theory of history, viewing architecture as the outcome of the role of the designer in the social division of labor, focusing on ‘modes of production’ in its explanations of the Gothic cathedral; 3. A History of Architecture: Settings and Rituals (1995), asserts a sociocultural nature for architecture and the Gothic cathedral, and hence studies it in terms of how it reflects the rituals held in it; 4. Architecture, from Prehistory to Postmodernity (2002), takes architecture as a spatio-visual monument-making art. According to this book in each monument, including the Gothic cathedral, the it's formal appearance, visual qualities of the space , and it's psychological effects are what make a work historically noteworthy.